"Teoriya" i "praktika" myzhskogo slaloma na poroge XXI veka: Anatomiya poluvekovoi nekompetentnosti federatsii gornolyzhnogo sporta - Oshchepkov, G. G. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
About the situation of mens slalom in Russia and the work and incompetence of the ski federation over years. Content e.g.: - scientific-methodological thoughts of coaches in alpine skiing concerning the technique, - new tendencies in international slalom and new perspectives of slalom in Russia - an individual experiment of the author.